Workload to Job Satisfaction : The Mediating Role of Work Life Balance At PT. Berlian Lautan Sejahtera - Fadhil Sahar Aqmar Nurcahyo; Dewie Tri Wijayati (Lavish Opulent Education, 2025)
This research aims to analyze the influence of workload on job satisfaction through work life balance on employees of PT Berlian Lautan Sejahtera. This research uses a quantitative approach. The population of this study were employees of PT Berlian Lautan Sejahtera and the sample size collected was 44 respondents. The data in this study were analyzed using SEM-PLS which was processed with SmartPLS 3.9.2 software. The analysis results obtained from this research show that workload has a negative and significant effect on job satisfaction. Workload has a negative and significant effect on work life balance. Work life balance has a positive and significant effect on job satisfaction. While in the analysis of the indirect effect of work life balance, it is able to mediate the influence of workload on job satisfaction.